Effects of Carbonate Alkalinity on Antioxidants, Immunity and Intestinal Flora of Penaeus vannamei - Chuang Gao; Zhonghong Li; Bo Ma; Rantao Zuo; Xudong Shen; Mingkang Chen; Chuanqi Ren; Wenjun Zheng; Zhonglu Cai; Jiaxing Li; Shuang Li (Fishes)
The purpose of this study was to investigate the physiological and biochemical changes of the hepatopancreas and intestinal microbial structure of Penaeus vannamei under various levels of carbonate alkalinity stress. After Penaeus vannamei (body length 14.24 ± 2.13 cm, body weight 26.31 ± 3.26 g) was subjected to 96 h carbonate alkalinity stress, the alkalinity stress levels were E8 (8 mmol/L), E18 (18 mmol/L) and E28 (28 mmol/L), respectively. The activity of antioxidant enzymes was determined by enzyme markers, and then the intestinal microorganisms of Penaeus vannamei were analyzed by high-throughput sequencing technology. The results showed that, under the stress of high carbonate alkalinity, the mortality rate of Penaeus vannamei was as high as 75%, and hepatopancreas cells showed obvious deformation, abnormal nuclear shapes, and serious cell vacuolation. Under high carbonate alkalinity stress, superoxide dismutase activity, catalase activity and glutathione peroxidase activity in the Penaeus vannamei hepatopancreas were significantly lower than those in control group (p < 0.05), and malondialdehyde content was significantly lower than that in the control group (p < 0.05). Alkaline phosphatase activity in the experimental group was significantly different from that in the control group (p < 0.05). Moreover, the 16SrDNA high-throughput sequencing results showed that the intestinal abundance of Proteobacteria in Penaeus vannamei was significantly decreased (p < 0.05) under high carbonate alkalinity stress, and the abundance of Bacteroides was significantly increased (p < 0.05). At the genus level, the abundance of Chrysobacteria was significantly increased (p < 0.05). The functional prediction results of COG and KEGG showed that the functional abundance of RNA polymerase sigma-70 factor is direct bacterial or plastid core RNA polymerase and is specific to promoter elements that are situated 10 and 35 base-pairs upstream of transcription-initiation points—in the high carbonate alkalinity treatment group, this was higher than that in the control group. The functional abundance of signal transduction histidine kinase was lower than that of the control group. The results of this study not only indicated that Penaeus vannamei cell structure would change and mortality would increase under high carbonate alkalinity culture environment, but they also analyzed the changes of the intestinal microbial structure under carbonate alkalinity stress. This study could provide theoretical reference for Penaeus vannamei saline–alkali land culture.